Crystal structure and Hirshfeld surface analysis of (Z)-4-{[4-(3-methyl-3-phenylcyclobutyl)thiazol-2-yl]amino}-4-oxobut-2-enoic acid - Simsek, Okan; Dincer, Muharrem; Dege, Necmi; Saif, Eiad; Yilmaz, Ibrahim; Cukurovali, Alaaddin (Int Union Crystallography, 2022)
The title cyclobutyl compound, C18H18N2O3S, was synthesized by the interaction of 4-(3-methyl-3-phenylcyclobutyl)thiazol-2-amine and maleic anhydride, and crystallizes in the orthorhombic space group P2(1)2(1)2(1) with Z' = 1. The molecular geometry is partially stabilized by an intramolecular N-H center dot center dot center dot O hydrogen bond forming an S-1(1)(7) ring motif. The molecule is non-planar with a dihedral angle of 88.29 (11)degrees between the thiazole and benzene rings. In the crystal, the molecules are linked by O-H center dot center dot center dot N hydrogen bonds, forming supramolecular ribbons with C-1(1)(9) chain motifs. To further analyze the intermolecular interactions, a Hirshfeld surface analysis was performed. The results indicate that the most important contributions to the overall surface are from H center dot center dot center dot H (43%), C center dot center dot center dot H (18%), O center dot center dot center dot H (17%) and N center dot center dot center dot H (6%), interactions.
Keywords: crystal structure; cyclobutyl; thiazole; 4-oxobut-2-enoic acid; Hirshfeld surface analysis